2017
DOI: 10.1016/j.molcel.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-Dependent Inactivation of the Groucho/TLE Co-repressor by the HECT E3 Ubiquitin Ligase Hyd/UBR5

Abstract: SummaryExtracellular signals are transduced to the cell nucleus by effectors that bind to enhancer complexes to operate transcriptional switches. For example, the Wnt enhanceosome is a multiprotein complex associated with Wnt-responsive enhancers through T cell factors (TCF) and kept silent by Groucho/TLE co-repressors. Wnt-activated β-catenin binds to TCF to overcome this repression, but how it achieves this is unknown. Here, we discover that this process depends on the HECT E3 ubiquitin ligase Hyd/UBR5, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 58 publications
(90 reference statements)
3
70
0
Order By: Relevance
“…If β‐catenin does not simply displace TLEs at W‐CRMs, how does Wnt signaling inactivate these co‐repressors? Another recent report from the Flack et al offers an intriguing mechanism. They found that the E3 ubiquitin‐protein ligase UBR5 (UBR5) is required for efficient Wnt signaling in HEK293 cells.…”
Section: Wnt‐dependent Ubiquitination Of Tles Regulates the Transcripmentioning
confidence: 98%
See 4 more Smart Citations
“…If β‐catenin does not simply displace TLEs at W‐CRMs, how does Wnt signaling inactivate these co‐repressors? Another recent report from the Flack et al offers an intriguing mechanism. They found that the E3 ubiquitin‐protein ligase UBR5 (UBR5) is required for efficient Wnt signaling in HEK293 cells.…”
Section: Wnt‐dependent Ubiquitination Of Tles Regulates the Transcripmentioning
confidence: 98%
“…C) This model postulated that these factors are also associated with TCF in Wnt‐stimulated cells, along with β‐catenin and other co‐activators. There is also evidence that TLEs are inactivated by ubiquitination via UBR5 (not shown) . In addition, newly discovered negative regulatory elements (NREs) are proposed to be bound by TCFs and β‐catenin, repressing transcription upon Wnt stimulation, fine‐tuning the transcriptional response of traditional W‐CRMs .…”
Section: Is the Transcriptional Switch A General Feature Of Wnt Gene mentioning
confidence: 99%
See 3 more Smart Citations